Competitiveness and growth of the Mexican economy - Daniel Chiquiar; Manuel Ramos-Francia (Banco de México, 2009)
We address the role that deep, structural factors may have as determinants of Mexico's economic growth. We argue that Mexico's poor growth performance appears to be associated not only with shorter-run events such as the lost decade of the eighties, but also with supply-side features of the economy that have been present for at least four decades. Mexico's low competitiveness and poor growth potential seem to reflect an institutional framework that tends to support rigid, non-competitive market structures, and incentives that promote the allocation of resources towards unproductive rent-seeking activities relatively more than into investment, production, and adoption of superior technologies. We present examples of input markets where we believe these issues are central. We conclude that solving this situation requires microeconomic policies that lead to fundamental changes in the incentive structure of the economy.
Keywords: O31; O43; O12; 330; competitiveness and growth; productivity; efficiency; comparative advantage